SUSTAINABLE DEVELOPMENT OF FUTURE FIRM REPUTATION - Vienda A Kuntjoro (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Purpose – The purpose of this paper is to explain whether sustainability development of firm reputation dimensions will enhance to perform and to reach firm reputation. Design/methodology/approach - The role of accounting research that is considered and supported accounting practice may help to provide accounting information related the investor decision making. This research is preliminary study and this research approaches based on explanatory with meta-analysis. In theory, the environment of accounting is both very complex and very challenging. The complex is because the product of accounting is information. The firm reputation dimensions seem important in terms of increasing the future firm reputation that could bring result of competition advantages. Finding – The principal finding of sustainable development of firm reputation adoption is to perform the expected firm growth.Original/value–The results of this study make contribution to quick response for investor to make investment decision on the outcomes of firm reputation should be the value to investor who wants the data accuracy and reliable accounting information.Keywords: sustainability development, sustainability development offirm reputation dimensions, accounting information.